Precursor with core-shell structure as well as preparation method and application of precursor
By adopting a precursor with a core-shell structure, using a porous intermediate layer and a La-Al doped shell layer, the problems of insufficient structural instability and mechanical stability of the ternary positive electrode material are solved, and high cyclic stability and electrochemical performance are improved.
Patent Information
- Application Number
- CN202510086654.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The existing ternary positive electrode materials have structural instability during recycling, resulting in material peeling and cycling performance degradation, and the porous structure positive electrode materials lack mechanical stability during charging and discharging.
The precursor adopting a core-shell structure includes a core, an intermediate layer and a shell layer. The intermediate layer is a porous structure, and the shell layer is doped with La and Al. It is prepared by co-precipitation method to form a La2Li0.5Al0.5O4 cladding layer to improve lithium ion transport and material protection.
The structural stability and cyclic performance of the positive electrode material are improved, the diffusion rate of lithium ions is enhanced, the structural changes of the material during charging and discharging are reduced, and the electrochemical reaction environment is optimized.
Smart Images

Figure CN119898828A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a core-shell structure precursor and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in the fields of power and energy storage due to their high energy density and good rate performance. With the rise of new energy vehicles, improving the endurance and energy storage capacity of lithium batteries has become a research hotspot.
[0003] Ternary cathode materials have attracted much attention due to their high specific capacity, but their cycling performance and safety issues limit their application. These problems are mainly due to the Li / Ni mixing and volume expansion and contraction during the cycle, which leads to the rupture of the material structure. At the same time, the side reaction between the cathode material surface and the electrolyte causes the battery performance to decline rapidly.
[0004] In order to solve these problems, researchers have achieved certain results by modifying the structure of the cathode material precursor or cathode material.
[0005] CN116924487A provides a method for preparing a porous precursor material. The invention introduces a pore-forming agent and cooperates with a two-step method to make the pores evenly distributed inside the precursor, increase the diffusion channel of lithium ions, make the capacity of the positive electrode material fully utilized, and significantly improve the electrochemical performance of the positive electrode material. However, the porous loose structure leads to a decrease in the compaction density of the material, affecting its stability in the charge and discharge cycle. In addition, during the preparation of the positive electrode material, the fine particles of the porous structure tend to migrate outward, and eventually form holes of different sizes and irregular multi-layer hollow ring structures inside the material. The irregularity of these structures further weakens the mechanical stability of the material.
[0006] CN118553890A discloses a ternary positive electrode material having a core-shell structure, including a titanium-doped low-nickel ternary positive electrode material coated with a carbon quantum dot CQDs layer located in the inner core and a high-nickel ternary positive electrode material and a B2O3 coating layer as a shell. 0.65 Co 0.07 Mn 0.28O2 doping with titanium enhances the structural stability of the material, and the CQDs coating layer improves the efficiency of electron and lithium ion transmission between the electrode and the electrolyte, thereby improving the rate and cycle performance of the ternary material; in addition, the high nickel ternary cathode material of the shell layer is combined with the core to effectively improve the overall capacity of the ternary cathode material. At the same time, a layer of B2O3 coated on the surface of the shell layer can reduce the corrosion of HF on the transition metal, alleviate the structural changes of the material during the charge and discharge process, and optimize the electrochemical reaction environment of the high nickel layer, thereby improving the capacity and cycle performance of the ternary lithium-ion battery. However, the element ratio between the core and shell of the core-shell material is significantly different, and this difference leads to significant differences in the microscopic morphology of the material, including the size of the primary particles, the pore structure, and the stacking mode of the particles. These differences may cause the separation of the core and the shell during the recycling of the material, and then cause the peeling of the cathode material. This structural instability seriously limits the cycle performance of the material, especially in the application of high nickel materials, and fails to fundamentally improve its cycle stability, thereby limiting its application potential in high-performance lithium-ion batteries.
[0007] Therefore, providing a modification strategy for high-performance cathode materials to enhance the lithium ion diffusion rate while improving the structural stability and cycle performance of the cathode materials is a technical problem that needs to be solved urgently. Summary of the invention
[0008] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a core-shell structure precursor and a preparation method and application thereof.
[0009] To achieve the above object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a precursor of a core-shell structure, wherein the ternary precursor of the core-shell structure comprises a core, an intermediate layer and a shell layer, wherein the intermediate layer is located between the core and the shell layer, the intermediate layer is a porous structure, the chemical composition of the core and the intermediate layer is a ternary compound, and the chemical composition of the shell layer is a ternary compound doped with La and Al.
[0011] The present invention provides a core-shell structure precursor. Since the intermediate layer has a loose porous structure, it can be used as a buffer layer to effectively reduce the generation of internal stress in the material and provide space for lithium ion storage. At the same time, the setting of the intermediate layer can prevent the problem of particle cracking due to stress during rapid dehydration, that is, it can avoid the cracking of the positive electrode material. Moreover, La and Al are doped in the shell layer, which can form lithium lanthanum aluminum oxide (such as La2Li 0.5 Al 0.5 O4) coating layer, which promotes the + transport and protect the positive electrode material from the corrosion of the electrolyte.
[0012] In the prior art methods, lithium salts (such as lithium carbonate or lithium hydroxide) may remain on the surface of the prepared positive electrode material. In the method of the present invention, since La and Al are doped in the shell layer of the precursor, the residual lithium salts can be reduced in the process of forming the lithium lanthanum aluminum oxide coating layer, thereby reducing the residual lithium salts in the positive electrode material.
[0013] The present invention provides a large-particle ternary precursor with a core-shell structure and a preparation method thereof. By combining core-shell structure design, ion doping and surface coating, the structural stability and cycle performance of the material are improved, while the diffusion rate of lithium ions is enhanced, and the precursor is suitable for preparing high-performance lithium-ion battery positive electrode materials.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] Preferably, the chemical composition of the core and the intermediate layer is nickel-cobalt-manganese hydroxide, and the chemical composition of the shell layer is nickel-cobalt-manganese hydroxide doped with La and Al.
[0016] In one embodiment, the molar ratios of nickel, cobalt and manganese are the same in each of the core, intermediate and shell layers.
[0017] Preferably, the total doping amount of La and Al in the shell layer is 1000ppm-5000ppm, for example, it can be 1000ppm, 1200ppm, 1400ppm, 1500ppm, 1750ppm, 2000ppm, 2200ppm, 2400ppm, 2700ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm or 5000ppm. If the doping amount of La and Al is too small, the formed lithium lanthanum aluminum oxide coating layer will be too thin or incomplete, which will not promote the Li + The role of La and Al in transporting and protecting the positive electrode material from electrolyte corrosion is weak; if the doping amount of La and Al is too much, the excessive doping element ions may affect the molecular structure of the ternary hydroxide, destroy the layered structure of the hydroxide, and affect the stability of the material structure.
[0018] Preferably, the molar ratio of La to Al is 1:4-4:1, for example, it can be 1:4, 1:3, 1:2, 1:1, 2:1, 3:1 or 4:1, etc., preferably 2:1-4:1.
[0019] Preferably, the thickness of the intermediate layer is 0.1 μm-2 μm, for example, 0.1 μm, 0.3 μm, 0.5 μm, 0.7 μm, 1 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.8 μm or 2 μm, preferably 0.2 μm-1.5 μm. If the intermediate layer is too thick, a fault may be formed at the connection, which eventually causes the core-shell inside the positive electrode material to separate, seriously affecting the battery performance; if the intermediate layer is too thin, it cannot play a role in reducing internal stress.
[0020] Preferably, the size of the inner core is 2 μm-5 μm, for example, 2 μm, 2.3 μm, 2.5 μm, 2.7 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.
[0021] Preferably, the shell layer has a thickness of 6 μm-11 μm, for example, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm or 11 μm.
[0022] Preferably, the primary particles of the core and the shell grow radially. This morphology is conducive to the transmission of lithium ions, thereby improving the electrochemical performance of the positive electrode material.
[0023] Preferably, the particle size D50 of the core-shell structure precursor is 8.1μm-17μm, for example, it can be 8.1μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, 16.5μm or 17μm, etc.
[0024] Preferably, the particle size span of the core-shell structure precursor is 0.3-0.6, for example, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55 or 0.6, etc. The particle size span is also called the diameter distance (span), which is an indicator of the particle size test, specifically calculated by (D90-D10) / D50.
[0025] Preferably, the specific surface area of the core-shell structure is 9 m 2 / g-15m 2 / g, for example, it can be 9m 2 / g, 9.5m 2 / g, 10m 2 / g, 10.5m 2 / g, 11m 2 / g, 11.5m 2 / g, 12m 2 / g, 12.5m2 / g, 13m 2 / g, 13.5m 2 / g, 14m 2 / g, 14.5m 2 / g or 15m 2 / g, etc.
[0026] Preferably, the tap density of the core-shell structure is 1.7 g / cm 3 -2.1g / cm 3 , for example, it can be 1.7 g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3 , 2.05g / cm 3 or 2.1 g / cm 3 wait.
[0027] In a second aspect, the present invention provides a method for preparing a precursor of a core-shell structure as described in the first aspect, the preparation method comprising the following steps:
[0028] (1) mixing a ternary metal salt solution, a precipitant solution and a complexing agent solution to perform a coprecipitation reaction, and stopping feeding after the particle size of the reaction product grows to a preset inner core particle size to obtain a seed crystal;
[0029] (2) mixing the seed crystals with water to form a base solution, and then adding a precipitant solution, a complexing agent solution and a ternary metal salt solution, controlling the amount of the precipitant solution and the complexing agent solution added, co-precipitating and reacting to grow and form an intermediate layer with a porous structure;
[0030] (3) The ternary metal salt solution of step (2) is replaced by a ternary metal salt solution to which aluminum salt and lanthanum salt are added, the amount of the precipitant solution and the complexing agent solution added is controlled, and the coprecipitation reaction is continued to obtain a core-shell structure precursor.
[0031] The invention prepares a precursor of a core-shell structure by a coprecipitation method. The preparation method is simple and suitable for industrial production.
[0032] In one embodiment, by controlling the amount of precipitant solution and complexing agent solution added, that is, in the middle layer growth stage, the pH and concentration of the complexing agent solution during the reaction are controlled at a lower level (compared to the growth of the core and shell), the primary particles grown at this time are relatively fine and flaky, thereby forming a porous middle layer. The pH and complexing agent concentration of the core and shell are higher, and the primary particles grown are relatively coarse, thereby being more dense.
[0033] In one embodiment, by controlling the stirring speed and the feeding rate of the mixed metal salt solution, that is, in the intermediate layer growth stage, the stirring speed and the feeding rate of the mixed metal salt solution during the reaction process are controlled at a lower level, while when growing the inner core and the shell layer, the stirring speed and the feeding rate of the mixed metal salt solution are controlled at a relatively high level.
[0034] As a preferred technical solution of the preparation method of the present invention, the ternary metal salt solution in step (1) includes nickel salt, cobalt salt and manganese salt.
[0035] Preferably, the total concentration of metal ions in the ternary metal salt solution in step (1) is 50 g / L-100 g / L, for example, it can be 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L or 100 g / L, etc.
[0036] Preferably, in step (1), the pH of the coprecipitation reaction is controlled between 11 and 13, for example, it can be 11, 11.2, 11.5, 11.7, 11.8, 12, 12.3, 12.6, 12.8 or 13, etc.
[0037] Preferably, in step (1), the coprecipitation reaction is carried out under stirring, and the stirring speed is controlled between 350rpm-420rpm, for example, it can be 350rpm, 360rpm, 380rpm, 400rpm, 410rpm or 420rpm.
[0038] Preferably, in step (1), the precipitant solution is a sodium hydroxide solution.
[0039] Preferably, in step (1), the concentration of the precipitant solution is 10wt%-30wt%, for example, it can be 10wt%, 12wt%, 13wt%, 15wt%, 17wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%, etc.
[0040] Preferably, in step (1), the complexing agent solution is aqueous ammonia.
[0041] Preferably, in step (1), the concentration of the complexing agent solution is 10wt%-20wt%, for example, it can be 10wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, etc.
[0042] Preferably, in step (1), the concentration of the complexing agent solution is controlled in the range of 10 g / L-15 g / L, for example, it can be 10 g / L, 10.5 g / L, 11 g / L, 11.5 g / L, 12 g / L, 12.5 g / L, 13 g / L, 13.5 g / L, 14 g / L, 14.5 g / L or 15 g / L, etc.
[0043] Preferably, in step (1), the feed rate of the ternary metal salt solution is controlled between 150 mL / min and 200 mL / min, for example, it can be 150 mL / min, 160 mL / min, 165 mL / min, 170 mL / min, 175 mL / min, 180 mL / min, 185 mL / min, 190 mL / min or 200 mL / min, etc.
[0044] Preferably, in step (1), the temperature of the coprecipitation reaction is 50°C-60°C, for example, it can be 50°C, 52°C, 53°C, 54°C, 56°C, 58°C or 60°C.
[0045] As a preferred technical solution of the preparation method of the present invention, the ternary metal salt solution in step (2) includes nickel salt, cobalt salt and manganese salt.
[0046] Preferably, the total concentration of metal ions in the ternary metal salt solution in step (2) is 50 g / L-100 g / L, for example, it can be 50 g / L, 55 g / L, 60 g / L, 65 g / L, 70 g / L, 75 g / L, 80 g / L, 85 g / L, 90 g / L, 95 g / L or 100 g / L, etc.
[0047] Preferably, in step (2), the pH of the coprecipitation reaction is controlled between 8 and 10, for example, it can be 8, 8.2, 8.3, 8.5, 8.6, 8.8, 9, 9.3, 9.5, 9.7, 9.8, 9.9 or 10, etc.
[0048] Preferably, in step (2), the coprecipitation reaction is carried out under stirring conditions, and the stirring speed is controlled between 250rpm-300rpm, for example, it can be 250rpm, 260rpm, 270rpm, 280rpm, 290rpm or 300rpm.
[0049] Preferably, in step (2), the precipitant solution is a sodium hydroxide solution.
[0050] Preferably, in step (2), the concentration of the precipitant solution is 10wt%-30wt%, for example, it can be 10wt%, 12wt%, 13wt%, 15wt%, 17wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%, etc.
[0051] Preferably, in step (2), the complexing agent solution is aqueous ammonia.
[0052] Preferably, in step (2), the concentration of the complexing agent solution is 10wt%-20wt%, for example, it can be 10wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, etc.
[0053] Preferably, in step (2), the concentration of the complexing agent solution is controlled in the range of 5 g / L-10 g / L, for example, it can be 5 g / L, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 7.5 g / L, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L or 10 g / L, etc.
[0054] Preferably, in step (2), the feed rate of the ternary metal salt solution is controlled between 100 mL / min and 150 mL / min, for example, it can be 100 mL / min, 105 mL / min, 110 mL / min, 115 mL / min, 120 mL / min, 125 mL / min, 130 mL / min, 135 mL / min, 140 mL / min, 145 mL / min or 150 mL / min, etc.
[0055] Preferably, in step (2), the temperature of the coprecipitation reaction is 50°C-60°C, for example, it can be 50°C, 52°C, 53°C, 54°C, 56°C, 58°C or 60°C.
[0056] As a preferred technical solution of the preparation method of the present invention, the ternary metal salt solution to which aluminum salt and lanthanum salt are added in step (3) comprises aluminum salt, lanthanum salt, nickel salt, cobalt salt and manganese salt.
[0057] Preferably, in the ternary metal salt solution to which aluminum salt and lanthanum salt are added in step (3), the concentration of aluminum ions is 50 mg / L-250 mg / L, for example, 50 mg / L, 60 mg / L, 80 mg / L, 100 mg / L, 120 mg / L, 130 mg / L, 150 mg / L, 160 mg / L, 180 mg / L, 190 mg / L, 200 mg / L, 210 mg / L, 220 mg / L, 230 mg / L, 240 mg / L, 250 mg / L, 260 mg / L, 270 mg / L, 280 mg / L, 290 mg / L, 300 mg / L, 310 mg / L, 320 mg / L, 330 mg / L, 340 mg / L, 360 mg / L, 370 mg / L, 380 mg / L, 390 mg / L, 400 mg / L, 410 mg / L, 420 mg / L, 430 mg / L, 440 mg / L, 450 mg / L, 460 mg / L, 470 mg / L, 480 mg / L, 490 mg / L, 500 mg / L, 510 mg / L, 520 mg / L, 530 mg / L, 540 mg / L, 550 mg / L the concentration of lanthanum ion is 50mg / L-250mg / L, for example, it can be 50mg / L, 60mg / L, 80mg / L, 100mg / L, 120mg / L, 130mg / L, 150mg / L, 160mg / L, 180mg / L, 190mg / L, 200mg / L, 210mg / L, 220mg / L, 230mg / L, 240mg / L or 250mg / L.
[0058] Preferably, in step (3), the pH of the coprecipitation reaction is controlled between 10 and 11, for example, it can be 10, 10.2, 10.3, 10.5, 10.6, 10.8 or 11, etc.
[0059] Preferably, in step (3), the coprecipitation reaction is carried out under stirring, and the stirring speed is controlled between 100 rpm and 250 rpm, for example, it can be 100 rpm, 110 rpm, 120 rpm, 130 rpm, 150 rpm, 160 rpm, 180 rpm, 200 rpm, 215 rpm, 225 rpm, 230 rpm, 240 rpm or 250 rpm, etc.
[0060] Preferably, in step (3), the precipitant solution is a sodium hydroxide solution.
[0061] Preferably, in step (3), the concentration of the precipitant solution is 10wt%-30wt%, for example, it can be 10wt%, 12wt%, 13wt%, 15wt%, 17wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt% or 30wt%, etc.
[0062] Preferably, in step (3), the complexing agent solution is aqueous ammonia.
[0063] Preferably, in step (3), the concentration of the complexing agent solution is 10wt%-20wt%, for example, it can be 10wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, etc.
[0064] Preferably, in step (3), the concentration of the complexing agent solution is controlled within the range of 8 g / L-10 g / L, for example, 8 g / L, 8.5 g / L, 9 g / L, 9.5 g / L or 10 g / L.
[0065] Preferably, in step (3), the feeding rate of the ternary metal salt solution to which aluminum salt and lanthanum salt are added is controlled between 50 mL / min and 130 mL / min, for example, it can be 50 mL / min, 55 mL / min, 60 mL / min, 65 mL / min, 70 mL / min, 75 mL / min, 80 mL / min, 85 mL / min, 90 mL / min, 95 mL / min, 100 mL / min, 105 mL / min, 110 mL / min, 115 mL / min, 120 mL / min, 125 mL / min or 130 mL / min, etc.
[0066] Preferably, in step (3), the temperature of the coprecipitation reaction is 50°C-60°C, for example, 50°C, 52°C, 53°C, 54°C, 56°C, 58°C or 60°C.
[0067] In the present invention, the types of nickel salts, cobalt salts, manganese salts, aluminum salts and lanthanum salts are not specifically limited. For example, nickel salts include but are not limited to at least one of nickel chloride, nickel nitrate or nickel sulfate; cobalt salts include but are not limited to at least one of cobalt nitrate, cobalt chloride or cobalt sulfate; manganese salts include but are not limited to at least one of manganese chloride, manganese nitrate or manganese sulfate; aluminum salts include but are not limited to aluminum sulfate and / or aluminum nitrate; lanthanum salts include but are not limited to lanthanum chloride and / or lanthanum nitrate.
[0068] In a third aspect, the present invention provides a positive electrode material, wherein the positive electrode material is prepared using the core-shell structure precursor described in the first aspect.
[0069] In a fourth aspect, the present invention provides a method for preparing the positive electrode material according to the third aspect, the preparation method comprising the following steps:
[0070] The core-shell structure precursor and the lithium source are mixed and sintered to obtain the positive electrode material.
[0071] The method of the present invention is to mix lithium and sinter the core-shell structure precursor, so that lithium enters the lattice of the precursor to form a positive electrode material. At the same time, on the one hand, since the intermediate layer of the precursor has a loose porous structure, the problem of particle cracking due to stress during rapid dehydration can be prevented; on the other hand, since La and Al are present in the shell layer of the precursor, lithium lanthanum aluminum oxide (such as La2Li 0.5 Al 0.5 O4), promoting Li+ transport and protect the positive electrode material from the corrosion of the electrolyte.
[0072] Preferably, the lithium salt comprises lithium carbonate and / or lithium hydroxide.
[0073] Preferably, the sintering is performed under a protective atmosphere.
[0074] Preferably, the gas in the protective atmosphere is at least one of nitrogen, argon, helium or neon.
[0075] Preferably, the sintering comprises pre-sintering and calcining performed sequentially.
[0076] Preferably, the pre-firing temperature is 500°C-600°C, for example, it can be 500°C, 525°C, 550°C, 560°C, 580°C or 600°C; the pre-firing time is 5h-10h, for example, it can be 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h.
[0077] Preferably, the calcination temperature is 600°C-900°C, for example, it can be 600°C, 625°C, 650°C, 670°C, 680°C, 700°C, 730°C, 760°C, 780°C, 800°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C, etc.; the calcination time is 10h-20h, for example, it can be 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, etc.
[0078] In a fifth aspect, the present invention provides a battery, comprising the positive electrode material described in the third aspect.
[0079] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0080] Compared with the prior art, the present invention has the following beneficial effects:
[0081] (1) The present invention provides a core-shell structure precursor. Since the intermediate layer has a loose porous structure, it can be used as a buffer layer to effectively reduce the generation of internal stress in the material and provide space for lithium ion storage. At the same time, the setting of the intermediate layer can prevent the problem of particle cracking due to stress during rapid dehydration, that is, it can avoid the cracking of the positive electrode material. Moreover, La and Al are doped in the shell layer, which can form lithium lanthanum aluminum oxide (such as La2Li 0.5Al 0.5 O4) coating layer, which promotes the + transport and protect the positive electrode material from the corrosion of the electrolyte.
[0082] (2) The present invention prepares the core-shell structure precursor by a co-precipitation method, which is simple and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 This is a SEM cross-sectional view of the ternary precursor prepared in Example 1. DETAILED DESCRIPTION
[0084] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0085] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0086] Example 1
[0087] This embodiment provides a large-particle ternary precursor with a core-shell structure, comprising a core, an intermediate layer and a shell layer, wherein the intermediate layer is located between the core and the shell layer, the intermediate layer is a porous structure, the chemical composition of the core and the intermediate layer is nickel-cobalt-manganese hydroxide, and the chemical composition of the shell layer is nickel-cobalt-manganese hydroxide doped with La and Al;
[0088] The doping amount of Al in the shell layer is 1000ppm, and the doping amount of La in the shell layer is 4000ppm;
[0089] The thickness of the intermediate layer is 0.2 μm.
[0090] The size of the core is 4 μm, the thickness of the shell is 10.8 μm, and the particle size D50 of the large-particle ternary precursor of the core-shell structure is 15 μm.
[0091] The particle size span of the core-shell structure precursor is 0.32, and the specific surface area of the core-shell structure is 13.8 m 2 / g, and the tap density of the core-shell structure is 1.83g / cm 3 .
[0092] This embodiment also provides a method for preparing the above-mentioned large-particle ternary precursor of the core-shell structure, comprising the following steps:
[0093] A nickel-cobalt-manganese ternary metal salt solution is prepared, wherein the molar ratio of Ni:Co:Mn is 0.9:0.05:0.05; the total concentration of metal ions is 100 g / L; the precipitant solution is a sodium hydroxide solution with a concentration of 20 wt%; the complexing agent solution is ammonia water with a concentration of 15 wt%; the above solution is used to perform the following steps:
[0094] Step (1): the feeding rate of nickel-cobalt-manganese ternary metal salt solution is 200 mL / min, the feeding rate of sodium hydroxide solution is 100 mL / min, the feeding rate of ammonia water is 25 mL / min, and the process parameters of the coprecipitation reaction are: pH is 12, the concentration of the complexing agent solution is 15 g / L, the reaction temperature is 60°C, the reaction stirring speed is 400 rpm, the feeding is stopped after the particle size D50 grows to 4.0 μm, and the seed crystal is obtained after washing.
[0095] Step (2): adding seed crystals to water to prepare a base solution, the feeding rate of nickel, cobalt and manganese ternary metal salt solution is 100 mL / min, the feeding rate of sodium hydroxide solution is 40 mL / min, and the feeding rate of ammonia water is 10 mL / min. The process parameters of the coprecipitation reaction are: pH is 9, the concentration of the complexing agent solution is controlled at 8 g / L, the reaction temperature is 60°C, the reaction stirring speed is 300 rpm, and the feeding is stopped after the particle size D50 grows to 4.2 μm.
[0096] Step (3): replacing the nickel-cobalt-manganese ternary metal salt solution with a mixed salt solution containing aluminum salt and lanthanum salt, wherein the molar ratio of Ni:Co:Mn is 0.9:0.05:0.05, the doping amount of Al is 1000ppm, the doping amount of La is 4000ppm, the feeding rate of the mixed metal salt solution is 130mL / min, the feeding rate of the sodium hydroxide solution is 50mL / min, and the feeding rate of the ammonia water is 12mL / min. The process parameters of the coprecipitation reaction are: pH is 11, the concentration of the complexing agent solution is controlled at 10g / L, the reaction temperature is 60°C, the reaction stirring speed is 150rpm, and the feeding is stopped after the particle size D50 grows to 15μm to obtain a large-particle ternary precursor with a core-shell structure.
[0097] like Figure 1 As shown, the SEM cross-sectional view of the ternary precursor prepared in this embodiment reveals its unique microstructure. The surface of the precursor is composed of small and relatively loose primary particles, and the interior thereof presents a distinct three-layer structure, specifically including a core, an intermediate layer, and a shell layer from the inside to the outside. Inside the core, a radial structure distributed from the inside to the outside can be seen. This structure runs through the intermediate layer and extends to the shell layer, forming an open channel from the center of the precursor to the surface. This radial porous structure provides a direct path for the rapid transmission of lithium ions, which is expected to improve the electrochemical properties of the material.
[0098] Example 2
[0099] This embodiment provides a large-particle ternary precursor with a core-shell structure, comprising a core, an intermediate layer and a shell layer, wherein the intermediate layer is located between the core and the shell layer, the intermediate layer is a porous structure, the chemical composition of the core and the intermediate layer is nickel-cobalt-manganese hydroxide, and the chemical composition of the shell layer is nickel-cobalt-manganese hydroxide doped with La and Al;
[0100] The doping amount of Al in the shell layer is 1000ppm, and the doping amount of La in the shell layer is 4000ppm;
[0101] The thickness of the intermediate layer is 0.2 μm.
[0102] The size of the core is 4 μm, the thickness of the shell is 10.8 μm, and the particle size D50 of the large-particle ternary precursor of the core-shell structure is 15 μm.
[0103] The particle size span of the core-shell structure precursor is 0.36, and the specific surface area of the core-shell structure is 14.2 m 2 / g, and the tap density of the core-shell structure is 1.8g / cm 3 .
[0104] This embodiment also provides a method for preparing the above-mentioned large-particle ternary precursor of the core-shell structure, comprising the following steps:
[0105] The molar ratio of Ni:Co:Mn in the nickel-cobalt-manganese ternary metal salt solution is 0.8:0.1:0.1; the total concentration of metal ions is 100 g / L; the precipitant solution is a sodium hydroxide solution with a concentration of 30 wt%; the complexing agent solution is ammonia water with a concentration of 20 wt%; the above solution is used to perform the following steps:
[0106] Step (1): the feeding rate of nickel, cobalt and manganese ternary metal salt solution is 200 mL / min, the feeding rate of sodium hydroxide solution is 80 mL / min, the feeding rate of ammonia water is 20 mL / min, and the process parameters of the coprecipitation reaction are: pH is 11, the concentration of the complexing agent solution is 10 g / L, the reaction temperature is 50°C, the reaction stirring speed is 350 rpm, the reaction is stopped when the particle size D50 grows to 4.0 μm, and the seed crystal is obtained after washing.
[0107] Step (2): adding seed crystals to water to prepare a base solution, the feeding rate of nickel, cobalt and manganese ternary metal salt solution is 100 mL / min, the feeding rate of sodium hydroxide solution is 30 mL / min, and the feeding rate of ammonia water is 6 mL / min. The process parameters of the coprecipitation reaction are: pH 8, the concentration of the complexing agent solution is controlled at 5 g / L, the reaction temperature is 50° C., the reaction stirring speed is 250 rpm, and the feeding is stopped after the particle size D50 grows to 4.2 μm.
[0108] Step (3): replacing the nickel-cobalt-manganese ternary metal salt solution with a mixed salt solution containing aluminum salt and lanthanum salt, wherein the molar ratio of Ni:Co:Mn is 0.8:0.1:0.1, the doping amount of Al is 1000ppm, the doping amount of La is 4000ppm, the feeding rate of the mixed metal salt solution is 130mL / min, the feeding rate of the sodium hydroxide solution is 40mL / min, and the feeding rate of the ammonia water is 10mL / min. The process parameters of the coprecipitation reaction are: pH is 10, the concentration of the complexing agent solution is controlled at 8g / L, the reaction temperature is 50°C, the reaction stirring speed is 100rpm, and the feeding is stopped after the particle size D50 grows to 15μm to obtain a large-particle ternary precursor with a core-shell structure.
[0109] After testing, the morphology of the ternary precursor of this embodiment is similar to that of Example 1. The surface of the precursor is composed of small and relatively loose primary particles, and the interior thereof presents a distinct three-layer structure, specifically including an inner core, an intermediate layer, and a shell layer from the inside to the outside. Inside the inner core, a radial structure distributed from the inside to the outside can be seen, which penetrates the intermediate layer and extends to the shell layer, forming an open channel from the center of the precursor to the surface.
[0110] Example 3
[0111] This embodiment provides a large-particle ternary precursor with a core-shell structure, comprising a core, an intermediate layer and a shell layer, wherein the intermediate layer is located between the core and the shell layer, the intermediate layer is a porous structure, the chemical composition of the core and the intermediate layer is nickel-cobalt-manganese hydroxide, and the chemical composition of the shell layer is nickel-cobalt-manganese hydroxide doped with La and Al;
[0112] The doping amount of Al in the shell layer is 1000ppm, and the doping amount of La in the shell layer is 4000ppm;
[0113] The thickness of the intermediate layer is 0.2 μm.
[0114] The size of the core is 4 μm, the thickness of the shell is 10.8 μm, and the particle size D50 of the large-particle ternary precursor of the core-shell structure is 15 μm.
[0115] The particle size span of the core-shell structure precursor is 0.33, and the specific surface area of the core-shell structure is 13.5 m 2 / g, and the tap density of the core-shell structure is 1.86 g / cm 3 .
[0116] This embodiment also provides a method for preparing the above-mentioned large-particle ternary precursor of the core-shell structure, comprising the following steps:
[0117] A nickel-cobalt-manganese ternary metal salt solution is prepared, wherein the molar ratio of Ni:Co:Mn is 0.7:0.1:0.2; the total concentration of metal ions in the ternary metal salt solution is 100 g / L; the precipitant solution is a sodium hydroxide solution with a concentration of 20 wt%; the complexing agent solution is ammonia water with a concentration of 10 wt%; the above solution is used to perform the following steps:
[0118] Step (1): the feeding rate of nickel, cobalt and manganese ternary metal salt solution is 200 mL / min, the feeding rate of sodium hydroxide solution is 120 mL / min, the feeding rate of ammonia water is 30 mL / min, and the process parameters of the coprecipitation reaction are: pH is 13, the concentration of the complexing agent solution is 15 g / L, the reaction temperature is 56°C, the reaction stirring speed is 420 rpm, the reaction is stopped when the particle size D50 grows to 4.0 μm, and the seed crystal is obtained after washing.
[0119] Step (2): adding seed crystals to water to prepare a base solution, the feeding rate of nickel, cobalt and manganese ternary metal salt solution is 100 mL / min, the feeding rate of sodium hydroxide solution is 50 mL / min, and the feeding rate of ammonia water is 10 mL / min. The process parameters of the coprecipitation reaction are: pH is 10, the concentration of the complexing agent solution is controlled at 10 g / L, the reaction temperature is 55° C., the reaction stirring speed is 280 rpm, and the feeding is stopped after the particle size D50 grows to 4.2 μm.
[0120] Step (3): replacing the nickel-cobalt-manganese ternary metal salt solution with a mixed salt solution containing aluminum salt and lanthanum salt, wherein the molar ratio of Ni:Co:Mn is 0.7:0.1:0.2, the doping amount of Al is 1000ppm, the doping amount of La is 4000ppm, the feeding rate of the mixed metal salt solution is 130mL / min, the feeding rate of the sodium hydroxide solution is 60mL / min, and the feeding rate of the ammonia water is 10mL / min. The process parameters of the coprecipitation reaction are: pH is 11, the concentration of the complexing agent solution is controlled at 10g / L, the reaction temperature is 55°C, the reaction stirring speed is 200rpm, and the feeding is stopped after the particle size D50 grows to 15μm to obtain a large-particle ternary precursor with a core-shell structure.
[0121] After testing, the morphology of the ternary precursor of this embodiment is similar to that of Example 1. The surface of the precursor is composed of small and relatively loose primary particles, and the interior thereof presents a distinct three-layer structure, specifically including an inner core, an intermediate layer, and a shell layer from the inside to the outside. Inside the inner core, a radial structure distributed from the inside to the outside can be seen, which penetrates the intermediate layer and extends to the shell layer, forming an open channel from the center of the precursor to the surface.
[0122] Example 4
[0123] This embodiment provides a large-particle ternary precursor with a core-shell structure. Compared with Embodiment 1, the only difference is that the size of the core is 1 μm and the thickness of the shell is 12.8 μm.
[0124] The difference between the preparation method of the large-particle ternary precursor of the core-shell structure mentioned above and Example 1 is that in step (1), the feeding is stopped after the reaction until the particle size D50 grows to 2.0 μm, in step (2), the feeding is stopped after the reaction until the particle size D50 grows to 2.2 μm, and in step (3), the final reaction particle size remains unchanged.
[0125] Example 5
[0126] This embodiment provides a large-particle ternary precursor with a core-shell structure. Compared with Embodiment 1, the only difference is that the size of the core is 6 μm and the thickness of the shell is 9.8 μm.
[0127] The difference between the preparation method of the large-particle ternary precursor of the core-shell structure mentioned above and Example 1 is that in step (1), the feeding is stopped after the reaction until the particle size D50 grows to 5.0 μm, in step (2), the feeding is stopped after the reaction until the particle size D50 grows to 5.2 μm, and in step (3), the final reaction particle size remains unchanged.
[0128] Example 6
[0129] This embodiment provides a large-particle ternary precursor with a core-shell structure. Compared with Embodiment 1, the only difference is that the thickness of the intermediate layer is 0.1 μm, and the thickness of the shell layer is 10.9 μm.
[0130] The difference between the preparation method of the core-shell structured large-particle ternary precursor and Example 1 is that in step (2), the feed is stopped after the particle size D50 grows to 4.1 μm, and in step (3), the final reaction particle size remains unchanged.
[0131] Example 7
[0132] This embodiment provides a large-particle ternary precursor with a core-shell structure. Compared with Embodiment 1, the only difference is that the thickness of the intermediate layer is 2 μm, and the thickness of the shell layer is 9 μm.
[0133] The difference between the method for preparing the large-particle ternary precursor of the core-shell structure described above and Example 1 is that in step (2), the feed is stopped after the particle size D50 grows to 6.0 μm, and in step (3), the final reaction particle size remains unchanged.
[0134] Example 8
[0135] This embodiment provides a large particle ternary precursor of a core-shell structure. Compared with Embodiment 1, the only difference is that the doping amount of Al in the shell layer is 2500ppm, and the doping amount of La in the shell layer is 2500ppm;
[0136] The difference between the preparation method of the core-shell structured large-particle ternary precursor and Example 1 is that in step (3), the doping amount of Al in the mixed salt solution containing aluminum salt and lanthanum salt is 2500 ppm, and the doping amount of La is 2500 ppm.
[0137] Example 9
[0138] This embodiment provides a large particle ternary precursor with a core-shell structure. Compared with Embodiment 1, the only difference is that the doping amount of Al in the shell layer is 4000ppm, and the doping amount of La in the shell layer is 1000ppm;
[0139] The difference between the above-mentioned method for preparing the large-particle ternary precursor of the core-shell structure and Example 1 is that in step (3), the doping amount of Al in the mixed salt solution containing aluminum salt and lanthanum salt is 4000 ppm, and the doping amount of La is 1000 ppm.
[0140] Example 10
[0141] This embodiment provides a large-particle ternary precursor with a core-shell structure, comprising a core, an intermediate layer and a shell layer, wherein the intermediate layer is located between the core and the shell layer, the intermediate layer is a porous structure, the chemical composition of the core and the intermediate layer is nickel-cobalt-manganese hydroxide, and the chemical composition of the shell layer is nickel-cobalt-manganese hydroxide doped with La and Al;
[0142] The doping amount of Al in the shell layer is 500ppm, and the doping amount of La in the shell layer is 1500ppm;
[0143] The thickness of the intermediate layer is 1 μm.
[0144] The size of the core is 3 μm, the thickness of the shell is 7 μm, and the particle size D50 of the large-particle ternary precursor of the core-shell structure is 11 μm.
[0145] The particle size span of the core-shell structure precursor is 0.45, and the specific surface area of the core-shell structure is 14.7 m 2 / g, and the tap density of the core-shell structure is 1.73g / cm 3 .
[0146] This embodiment also provides a method for preparing the above-mentioned large-particle ternary precursor of the core-shell structure, comprising the following steps:
[0147] A nickel-cobalt-manganese ternary metal salt solution is prepared, wherein the molar ratio of Ni:Co:Mn is 0.9:0.05:0.05; the total metal ion concentration is 70 g / L; the precipitant solution is a sodium hydroxide solution with a concentration of 15 wt%; the complexing agent solution is ammonia water with a concentration of 15 wt%; and the above solution is used to perform the following steps:
[0148] Step (1): the feeding rate of nickel-cobalt-manganese ternary metal salt solution is 150 mL / min, and the process parameters of the coprecipitation reaction are: pH 11.5, the concentration of the complexing agent solution is 12 g / L, the reaction temperature is 55° C., the reaction stirring speed is 375 rpm, and the feeding is stopped after the particle size D50 grows to 3.0 μm, and the seed crystal is obtained after washing.
[0149] Step (2): adding seed crystals into water to prepare a base solution, the feeding rate of nickel, cobalt and manganese ternary metal salt solution is 100 mL / min, and the process parameters of the coprecipitation reaction are: pH is 8, the concentration of the complexing agent solution is controlled at 5 g / L, the reaction temperature is 50° C., the reaction stirring speed is 250 rpm, and the feeding is stopped after the particle size D50 grows to 4.0 μm.
[0150] Step (3): replacing the nickel-cobalt-manganese ternary metal salt solution with a mixed salt solution containing aluminum salt and lanthanum salt, wherein the molar ratio of Ni:Co:Mn is 0.9:0.05:0.05, the doping amount of Al is 1500ppm, the doping amount of La is 1500ppm, the feeding rate of the mixed metal salt solution is 85mL / min, and the process parameters of the coprecipitation reaction are: pH is 10.5, the concentration of the complexing agent solution is controlled at 8g / L, the reaction temperature is 55°C, the reaction stirring speed is 250rpm, and the feeding is stopped after the particle size D50 grows to 11μm to obtain a large-particle ternary precursor with a core-shell structure.
[0151] After testing, the morphology of the ternary precursor of this embodiment is similar to that of Example 1. The surface of the precursor is composed of small and relatively loose primary particles, and the interior thereof presents a distinct three-layer structure, specifically including an inner core, an intermediate layer, and a shell layer from the inside to the outside. Inside the inner core, a radial structure distributed from the inside to the outside can be seen, which penetrates the intermediate layer and extends to the shell layer, forming an open channel from the center of the precursor to the surface.
[0152] Comparative Example 1
[0153] This comparative example provides a core-shell structured large particle ternary precursor, which is different from Example 1 only in that reaction step (2) is not performed, that is, no intermediate layer is formed.
[0154] Comparative Example 2
[0155] This comparative example provides a large-particle ternary precursor with a core-shell structure. Compared with Example 1, the only difference is that in the reaction step (3), the doping amounts of Al and La in the mixed salt solution containing aluminum salt and lanthanum salt are both 0, that is, no element doping is performed.
[0156] Comparative Example 3
[0157] This comparative example provides a large-particle ternary precursor with a core-shell structure. Compared with Example 1, the only difference is that in the reaction step (3), the doping amount of Al in the mixed salt solution containing aluminum salt and lanthanum salt is 0, while the doping amount of La is 5000 ppm.
[0158] Comparative Example 4
[0159] This comparative example provides a large-particle ternary precursor with a core-shell structure. Compared with Example 1, the only difference is that in the reaction step (3), the doping amount of Al in the mixed salt solution containing aluminum salt and lanthanum salt is 5000 ppm, and the doping amount of La is 0.
[0160] The core-shell structured large particle ternary precursors obtained in the above Examples 1-10 and Comparative Examples 1-4 were uniformly mixed with lithium hydroxide, pre-calcined in a muffle furnace at 500° C. for 5 h, and then further calcined at 850° C. for 20 h to obtain a positive electrode material.
[0161] The positive electrode material is prepared into a positive electrode sheet by the following preparation method: adding the positive electrode material, Super P and PVDF into NMP according to a mass ratio of 95:2:3, mixing evenly to obtain a positive electrode slurry, coating the positive electrode slurry on an aluminum foil, and drying to obtain a positive electrode sheet.
[0162] The positive electrode sheet, the lithium sheet and the polypropylene separator are prepared into a battery core, and the battery core is placed in a battery shell and then an electrolyte is injected, wherein the electrolyte is a 1 mol / L lithium hexafluorophosphate electrolyte to obtain a lithium ion battery.
[0163] The electrochemical performance of the lithium-ion battery was tested at 25°C, in the voltage range of 2.7-4.3V, and a current density of 1C.
[0164] The test results are shown in the following table:
[0165] Table 1
[0166]
[0167]
[0168] From Table 1 we can see that:
[0169] (1) It can be seen from Examples 1 to 3 and Example 10 that the large-particle ternary precursor with a core-shell structure provided by the present invention has excellent cycle stability. At a current density of 1C, the initial specific capacity is above 174 mAh / g, and the capacity retention rate after 100 cycles can reach more than 93%.
[0170] (2) It can be seen from Example 1 and Examples 4 to 5 that, when the thickness of the intermediate layer and the particle size of the precursor remain unchanged, if the size of the core is too small, the capacity retention rate of the positive electrode material will decrease.
[0171] (3) It can be seen from Examples 1 and 6-7 that, when the size of the core and the particle size of the precursor remain unchanged, if the intermediate layer is too thick, a fault may be formed at the connection, which will eventually cause the core and shell inside the positive electrode material to separate, seriously affecting the battery performance; if the intermediate layer is too thin, it will not be able to reduce the internal stress. Therefore, if the thickness of the intermediate layer is too small or too large, the capacity retention rate of the positive electrode material will decrease.
[0172] (4) It can be seen from Example 1 and Examples 8 to 9 that the use of an appropriate doping ratio for doping Al and La can better achieve the growth of the precursor and further improve the rate performance and cycle stability of the battery. The preferred molar ratio of La to Al is 2:1-4:1.
[0173] (5) From the data results of Example 1 and Comparative Example 1, it can be seen that the intermediate layer of the precursor material provided by the present invention can be used as a buffer layer, which effectively reduces the generation of internal stress and improves the structural stability and cycle performance of the material.
[0174] (6) From the data results of Example 1 and Comparative Examples 2-4, it can be seen that the doping of Al and La can form lithium aluminum lanthanum oxide (such as La2Li 0.5 Al 0.5 O4) coating layer, which promotes the + It improves the transmission of materials and protects them from the corrosion of electrolytes, thus improving the structural stability and cycle performance of materials.
[0175] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A core-shell structure precursor, characterized in that: The core-shell structured ternary precursor comprises a core, an intermediate layer and a shell layer, wherein the intermediate layer is located between the core and the shell layer, the intermediate layer is a porous structure, the chemical composition of the core and the intermediate layer is a ternary compound, and the chemical composition of the shell layer is a ternary compound doped with La and Al.
2. The core-shell structure precursor according to claim 1, characterized in that: The chemical composition of the core and the intermediate layer is nickel-cobalt-manganese hydroxide, and the chemical composition of the shell layer is nickel-cobalt-manganese hydroxide doped with La and Al; Preferably, the total doping amount of La and Al in the shell layer is 1000ppm-5000ppm; Preferably, the molar ratio of La to Al is 1:4-4:1, preferably 2:1-4:1; Preferably, the thickness of the intermediate layer is 0.1 μm-2 μm, preferably 0.2 μm-1.5 μm.
3. The core-shell structure precursor according to claim 1 or 2, characterized in that: The size of the core is 2 μm-5 μm; Preferably, the thickness of the shell layer is 6 μm-11 μm; Preferably, the primary particles of the core and the shell both grow radially; Preferably, the particle size D50 of the core-shell structure precursor is 8.1 μm-17 μm; Preferably, the particle size span of the core-shell structure precursor is 0.3-0.6; Preferably, the specific surface area of the core-shell structure is 9 m 2 / g-15m 2 / g; Preferably, the tap density of the core-shell structure is 1.7 g / cm 3 -2.1g / cm 3 .
4. A method for preparing a core-shell structure precursor according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a ternary metal salt solution, a precipitant solution and a complexing agent solution to perform a coprecipitation reaction, and stopping feeding after the particle size of the reaction product grows to a preset inner core particle size to obtain a seed crystal; (2) mixing the seed crystals with water to form a base solution, and then adding a precipitant solution, a complexing agent solution and a ternary metal salt solution, controlling the amount of the precipitant solution and the complexing agent solution added, co-precipitating and reacting to grow and form an intermediate layer with a porous structure; (3) The ternary metal salt solution of step (2) is replaced by a ternary metal salt solution to which aluminum salt and lanthanum salt are added, the amount of the precipitant solution and the complexing agent solution added is controlled, and the coprecipitation reaction is continued to obtain a core-shell structure precursor.
5. The preparation method according to claim 4, characterized in that: The ternary metal salt solution in step (1) comprises nickel salt, cobalt salt and manganese salt; Preferably, the total concentration of metal ions in the ternary metal salt solution in step (1) is 50 g / L-100 g / L; Preferably, in step (1), the pH of the coprecipitation reaction is controlled between 11 and 13; Preferably, in step (1), the coprecipitation reaction is carried out under stirring, and the stirring speed is controlled between 350 rpm and 420 rpm; Preferably, in step (1), the precipitant solution is a sodium hydroxide solution; Preferably, in step (1), the concentration of the precipitant solution is 10wt%-30wt%; Preferably, in step (1), the complexing agent solution is aqueous ammonia; Preferably, in step (1), the concentration of the complexing agent solution is 10wt%-20wt%; Preferably, in step (1), the concentration of the complexing agent solution is controlled within the range of 10 g / L-15 g / L; Preferably, in step (1), the feeding rate of the ternary metal salt solution is controlled between 150 mL / min and 200 mL / min; Preferably, in step (1), the temperature of the coprecipitation reaction is 50°C-60°C.
6. The preparation method according to claim 4 or 5, characterized in that: The ternary metal salt solution in step (2) comprises nickel salt, cobalt salt and manganese salt; Preferably, the total concentration of metal ions in the ternary metal salt solution in step (2) is 50 g / L-100 g / L; Preferably, in step (2), the pH of the coprecipitation reaction is controlled between 8 and 10; Preferably, in step (2), the coprecipitation reaction is carried out under stirring, and the stirring speed is controlled between 250 rpm and 300 rpm; Preferably, in step (2), the precipitant solution is a sodium hydroxide solution; Preferably, in step (2), the concentration of the precipitant solution is 10wt%-30wt%; Preferably, in step (2), the complexing agent solution is aqueous ammonia; Preferably, in step (2), the concentration of the complexing agent solution is 10wt%-20wt%; Preferably, in step (2), the concentration of the complexing agent solution is controlled within the range of 5 g / L-10 g / L; Preferably, in step (2), the feeding rate of the ternary metal salt solution is controlled between 100 mL / min and 150 mL / min; Preferably, in step (2), the temperature of the coprecipitation reaction is 50°C-60°C.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The ternary metal salt solution to which aluminum salt and lanthanum salt are added in step (3) comprises aluminum salt, lanthanum salt, nickel salt, cobalt salt and manganese salt; Preferably, in the ternary metal salt solution to which aluminum salt and lanthanum salt are added in step (3), the concentration of aluminum ions is 50 mg / L-250 mg / L, and the concentration of lanthanum ions is 50 mg / L-250 mg / L; preferably, in step (3), the pH of the coprecipitation reaction is controlled between 10 and 11; Preferably, in step (3), the coprecipitation reaction is carried out under stirring, and the stirring speed is controlled between 100 rpm and 250 rpm; Preferably, in step (3), the precipitant solution is a sodium hydroxide solution; Preferably, in step (3), the concentration of the precipitant solution is 10wt%-30wt%; Preferably, in step (3), the complexing agent solution is aqueous ammonia; Preferably, in step (3), the concentration of the complexing agent solution is 10wt%-20wt%; Preferably, in step (3), the concentration of the complexing agent solution is controlled within the range of 8 g / L-10 g / L; Preferably, in step (3), the feeding rate of the ternary metal salt solution to which the aluminum salt and the lanthanum salt are added is controlled between 50 mL / min and 130 mL / min; Preferably, in step (3), the temperature of the coprecipitation reaction is 50°C-60°C.
8. A positive electrode material, characterized in that The positive electrode material is prepared using the core-shell structure precursor according to any one of claims 1 to 3.
9. A method for preparing a positive electrode material as claimed in claim 8, characterized in that: The preparation method comprises the following steps: The core-shell structure precursor and the lithium source are mixed and sintered to obtain the positive electrode material; Preferably, the lithium salt comprises lithium carbonate and / or lithium hydroxide; Preferably, the sintering is carried out under a protective atmosphere; Preferably, the gas in the protective atmosphere is at least one of nitrogen, argon, helium or neon; Preferably, the sintering comprises pre-sintering and calcining performed sequentially; Preferably, the pre-burning temperature is 500°C-600°C, and the pre-burning time is 5h-10h; Preferably, the calcination temperature is 600° C.-900° C., and the calcination time is 10 h-20 h.
10. A battery, characterized in that: The battery comprises the positive electrode material according to claim 8.
Citation Information
Cited By
Ternary positive electrode core-shell precursor material, preparation method thereof, ternary positive electrode material and lithium ion battery
CN121672601A